The emptiness formation probability correlation in homogeneous and dimerized XX chains - Stolze, J.; Garske, T. (Condensed Matter Physics, 2009)
We review some known properties of the emptiness formation probability correlation which we have calculated
numerically for spin-1/2 XX chains with constant (homogeneous) or alternating (dimerized) nearestneighbor
coupling and an external field (in z direction) for arbitrary temperature. The long-distance asymptotic
behavior of this correlation is known to be Gaussian at zero temperature and exponential at finite temperature
for the homogeneous chain. By simple analytical arguments the exponential behavior at finite temperature
extends to the dimerized system. Numerical results for the dimerized chain confirm the exponential decay at
finite temperature and show Gaussian decay at zero temperature. Ми оглядаємо деякi вiдомi властивостi кореляцiї “ймовiрностi утворення порожнини”, яку ми обчислюємо чисельно для спiн-1/2 XX ланцюжкiв з сталими (однорiдними) або змiнними (димеризованими) взаємодiями найближчих сусiдiв i зовнiшнiм полем (у z напрямку) при довiльнiй температурi. Для однорiдного ланцюжка асимптотична поведiнка на великих вiдстанях цiєї кореляцiї є гаусова при нульовiй температурi i експоненцiйна при скiнченiй температурi. Простими аналiтичними аргументами експоненцiйна поведiнка при скiнченiй температурi поширюється i на димеризовану систему. Чисельнi результати для димеризованого ланцюжка пiдтверджують експоненцiйне згасання при скiнченiй температурi i дають гаусове згасання при нульовiй температурi.